The Analysis of Influencing Factors and Characteristics of Chinese Painting in Song Dynasty (960-1279 Ad) - Wang , Mo; Phu-ngamdee, Sakon (Journal of Roi Kaensarn Academi, 2024)
The following research is explored in this paper: This study aims to identify the key factors that shaped the artistic characteristics of Chinese paintings during the Song Dynasty. This paper seeks to elucidate the relationship and role between the artistic characteristics of Chinese paintings in the Song Dynasty and the influencing factors. What part can the relationship between the factors that formed Chinese paintings in the Song Dynasty play in the fields of contemporary art education, social art development, and personal art development? The objective of this research is to: 1. To analyze and study the factors and categories that influence the artistic characteristics of Chinese painting in the Song Dynasty. 2. To determine the relationship and role of the formal and aesthetic characteristics of Song Dynasty Chinese paintings with influencing factors. 3. To explore the relationship between the formation factors of Song Dynasty Chinese painting and its impact on contemporary art education, social art development, and personal art development. In this study, data were collected through the administration of questionnaires and the conduct of expert interviews, and subsequently verified through the utilisation of a range of analytical techniques, including descriptive statistics, difference analysis, correlation analysis, structural equation modelling (SEM) validation, consistency analysis and other methods. In conclusion, This thesis examines the factors and characteristics that shaped Chinese painting during the Song Dynasty (960-1279 AD). It finds that political stability and turmoil influenced the style and subject matter of painting, economic development fostered the painting market and innovation, social and cultural changes and religious diffusion enriched the content of painting, artistic exchanges enhanced expressiveness, and the development of the academy system promoted the systematization of painting theory and practice. In conclusion, the development of the Song Dynasty and the characteristics of the times still have value in terms of systematic research on the reform of modern Chinese painting education and the college system. This is particularly relevant in the current social environment, in order to meet the needs of social development and the people's overall improvement of aesthetic literacy.